2020
DOI: 10.1016/j.bbr.2019.112414
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of prior stress on conditioned inhibition of fear and fear extinction

Abstract: Resistant and generalized fear are hallmark symptoms of Post-Traumatic Stress Disorder (PTSD). Given PTSD is highly comorbid with addiction disorders indicates a maladaptive interaction between fear and reward circuits. To investigate learning processes underlying fear, reward and safety, we trained male rats to discriminate among a fear cue paired with footshock, a reward cue paired with sucrose and an explicit safety cue co-occurring with the fear cue in which no footshocks were delivered. In an attempt to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Further, our population appeared biased towards goal-tracking behavior (Fig 2G;Fitzpatrick et al, 2013), therefore using rats from a supplier whose population demonstrates greater levels of sign-tracking behavior, or a different strain of rat may be an important consideration for future work. However, the reductions in goal-tracking behavior in the TMT-exposed rats is particularly interesting and similar reductions in reward approach behavior have been observed in rats following repeated footshock stress (Woon et al, 2019). One interpretation of this data pattern is that TMT exposure induced an anhedonia-like phenotype, a well-defined symptom of PTSD (APA, 2013, Nawijn et al, 2015, Vujanovic et al, 2017, such that a decrease in sucrose reward led to a decrease in goal-tracking behavior in the task.…”
Section: Discussionsupporting
confidence: 55%
“…Further, our population appeared biased towards goal-tracking behavior (Fig 2G;Fitzpatrick et al, 2013), therefore using rats from a supplier whose population demonstrates greater levels of sign-tracking behavior, or a different strain of rat may be an important consideration for future work. However, the reductions in goal-tracking behavior in the TMT-exposed rats is particularly interesting and similar reductions in reward approach behavior have been observed in rats following repeated footshock stress (Woon et al, 2019). One interpretation of this data pattern is that TMT exposure induced an anhedonia-like phenotype, a well-defined symptom of PTSD (APA, 2013, Nawijn et al, 2015, Vujanovic et al, 2017, such that a decrease in sucrose reward led to a decrease in goal-tracking behavior in the task.…”
Section: Discussionsupporting
confidence: 55%
“…Excitingly, we could clearly distinguish the more reward-generalized mice from the more aversion-generalized mice by this novel go/go paradigm, although the paradigm may be further improved to reduce the difficulty differences between poking for reward and stepping on platform for aversive avoidance. Woon et al has previously reported that prior stress could significantly reduce reward seeking behaviours to a reward-associated cue during training 38 . In our go/go paradigm, we found a dramatical reduction of reward-generalized approaching in mice with more aversive generalization, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a ‘no-go’ as a response indicator cannot be distinguished from a response omission. Inspired by platform-mediated avoidance 35 37 and discriminative conditioning 16 , 38 , we developed a new go/go task in the present study. We first trained the mice to poke for sucrose reward associated with one tone and to step on an insulated platform in response to a different tone to avoid foot-shock punishment.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of biological and environmental factors–such as current and prior exposure to trauma–are likely to contribute to individual differences in the extent to which adolescents benefit from safety learned via conditioned inhibition. Importantly, whereas stress disrupts extinction learning, recent evidence in rodents suggests that safety signals may be a robust approach to fear reduction even following stress—rodents exposed to prior stress showed impaired fear extinction, but no disruption in conditioned inhibition 26 . Moreover, evidence in rodents suggests that adolescence may be a unique period when conditioned inhibition is robust to effects of stress experienced in childhood 27 .…”
Section: Reducing Fear Via Safety Signal Learningmentioning
confidence: 99%